“Guru Pintar Online” As Open Education Resources to Improve the Quality of Mathematics Instruction in Elementary School - Mery Noviyanti; Della R. Jovanka (International Conference on Education and Language (ICEL), 2013)
Teaching mathematics in elementary school is not easy, it needs competencies to make the mathematical abstract concepts into concrete.The children’s thinking ability is still at concrete operations stages. Therefore, the teacher must have the skills to handle the students.  In relation with this, the teacher should always develop his/her profesionalism  to improve the quality of teaching. “Guru Pintar Online” (GPO) is one of relevant open educational resources to support teaching and learning delivery. “Laboratorium Pembelajaran” is one of the GPO facilities that contains some collections of case studies’ video streaming and also provide a sample solution. In addition, teachers are given the opportunity to provide feedback and other solutions to solve the cases. This article will describe what strategies are offered through “Laboratorium Pembelajaran GPO” and usefulness analysis of this facility especially mathematics instruction in elementary school.